Price Co-Movement between Biodiesel and Natural Gas - JANDA, Karel; KOURILEK, Jakub; TRABELSI, Sarah (Journal of Environmental Management and Tourism, 2017)
We study relationship between biodiesel, as a most important biofuel in the European Union, relevant feedstock commodities and fossil fuels. Our main interest is to capture relationship between biodiesel and natural gas. They are both used either directly as a fuel or indirectly in form of additives in transport. Therefore, our purpose is to find price linkage between biofuel and natural gas to support or reject the claim that they compete as alternative fuels and potential substitutes. The estimated price link between biodiesel and diesel is negative and the strongest among analyzed commodities. The price transmission between biodiesel and natural gas is the weakest one.